Convergence Epistemologies of Legal Studies Perspectives of Islamic Philosophy - Yogi Prasetyo; Absori Absori (Institut Agama Islam Negeri (IAIN) Salatiga, 2018)
Epistemology of knowledge, also epistemology of legal studies, which is derived from the senses, rationality, and inner voices, has their own analysis methods to attain truths; inductive reasoning to seek validity of empirical knowledge, deductive reasoning for knowledge based on reason or rationality, and intuition for that derived from inner voices. The three analysis methods often lead to debate and contradicting claims creating a conflicting truth in epistemology.This conflicting claims of truth results in stagnancy, deviation, and distortion, in which the truth attained during the process may be misused for certain parties, since in the field of law, truth may be established to accommodate one’s needs. Therefore, it is crucial to create a concept which reconciles various epistemologies in knowledge, as well in legal studies, which is through a convergence of epistemology in legal studies through the perspective of Islamic philosophy. Through Islamic philosophy which is based on Quran, a conflicting knowledge derived through the senses, rationality, and inner voices will reconcile in one central point.Islamic philosophy which is based on Quran is the basis for epistemological truth derived from the senses, rationality, and inner voices, to simultaneously and jointly understand and complement each others’ strengths and weaknesses through a circular triadic process in order to reach reconciliation.